Strategi Pengembangan Industri Kreatif Kerajinan Purun di Kampung Purun Kota Banjarbaru - Arifin, Zainal; Nuryadin, Muhammad Rusmin (PPJP ULM, 2023)
This study aims (1) to explain internal factors that are strengths and weaknesses in the economic development of the community in Purun Village, (2) to explain external factors that are opportunities and threats to community economic development in Purun Village, (3) to explain creative industry development strategies Purun crafts in the right Purun Village. This study uses FGD (focus group discussion) by selecting competent people in fields related to Purun woven crafts in Purun Village, Banjarbaru City. The results of this study indicate that the strategy for developing the creative industry of pure handicrafts is in quadrant IV, which produces a W-O strategy as follows: (1) Looking for alternative run dryer technology to facilitate production so that it can expand to a broader market share. (2) Regulate business management properly to expand marketing.